The Politics of Black Joy Zora Neale Hurston and Neo-Abolitionism - Stewart, Lindsey (LIndsey L.) (Book collections on Project MUSE., 2021)
"In the Politics of Black Joy, Lindsey Stewart develops Hurston's contributions to political theory and philosophy of race by introducing the politics of joy as a refusal of neoabolitionism, a political tradition that reduces southern Black life to tragedy or social death"--